Re-imagining the NS/NNS dichotomy: bicultural teachers - Fathelbab, Heba H. (AUC Knowledge Fountain, 2010)
EFL teachers have been categorized using the NS/NNS (native speaker/non-native speaker) dichotomy into NESTs (native English speaking teachers) and NNESTs (non-native English speaking teachers). However, this inaccurate dichotomy does not take into account other possible categories that may fall between these two extreme notions, and has shown to have several ramifications. First, students' perception of teacher nativeness may influence students' attitudes and learning (Sahin, 2005). In addition, this perception could have an effect on students' evaluations of their teachers (Al-Issa & Sulieman, 2007). Further, this biased dichotomy contributes to NNESTs' low self-confidence (Butler, 2007). Finally, it may cause unequal job opportunities in the EFL market (Canagarajah, 1999). This qualitative study explores how students identify the ideal EFL teacher and how they perceive bicultural teachers (BCTs). BCTs represent one of many categories that do not fit in the dichotomy and are defined as teachers that have acquired native or near native competence in two languages. They have also been immersed in the cultures of both languages, where one of these two languages is the mother tongue of the learners. The participants included 61 undergraduate and 32 graduate upper-intermediate EFL students at the American University in Cairo. The students were surveyed on their opinions about teacher nativeness and the ideal teacher using a questionnaire. In addition, focus groups were conducted to clarify the results obtained from the questionnaire. Results show that students perceive the ideal teacher as possessing a combination of different qualities, only some of which are influenced by nativeness. In addition, students have difficulty identifying BCTs, although a few students are able to see beyond the dichotomy and use a different conceptual approach to identify them. Moreover, once students are able to identify BCTs, they see them as possibly highly competent teachers that combine qualities of both NESTs and NNESTs. Results also imply that the NS fallacy still exists as the participants tended to associate accent, appearance and names with teacher-competence. Therefore, the dichotomy should be modified so that the EFL community will refrain from judging teachers based on a pre-conceived notion of the NEST being the ideal EFL teacher.